Online Classes during COVID-19 Pandemic in Higher Learning Institutions in Africa - Paschal, Mahona, Joseph; Mkulu, Demetria, Gerold (My University, 2021)
During COVID-19 period students usually had to go to a physical place for learning. Nonetheless, the outbreak of the COVID-19 has birthed an array of highly creative innovations that have cut across several industries but has exposed the lack of technology in these sectors including the already fragmented education sector of African countries which needs restructuring and transforming. Many public and private Universities have had to be reactive but face steep contextual challenges in the conventional methods of creating, delivering, and capturing value in the education sector. This paper aimed to investigate online classes during the COVID-19 pandemic in different universities in Africa with a focus on five universities. The study adopted the Constructivist Theory. The research was guided by three main objectives including (1) To explore the effectiveness of online education in African Universities; (2) To assess the challenges facing online classes during COVID-19 in African universities; and (3) To determine possible strategies to curb challenges facing online education in higher learning institutions during COVID-19 and post-pandemic in Africa. The study employed a qualitative and quantitative method in data collection. The targeted population is lecture students from five Universities in African countries including Tanzania. The result of the study indicated that students learned more in less time and liked their classes more when ICT-based instruction was included. Notwithstanding, the majority of the participants demonstrated that learners in higher institutions in Africa have trouble accessing the E-learning technology system.
Keywords: African Universities; COVID-19 pandemic; online higher education; online teaching; reshaping online learning